Forms of Realizing the Right to Freedom of Peaceful Assembly - М. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
It has been grounded that the right to freedom of peaceful assembly is a unique right that unites the right and freedom of its realization. The realization of this right by some subjects, as well as the obligation of public administration subjects to create conditions for the unimpeded realization of the right to freedom of peaceful assembly require an understanding of the outer shell (form) of realizing the right to freedom of peaceful assembly.